PTH-181 Eosinophilic oesophagitis in the uk is not associated with a diminution in quality of life. (22nd June 2015) - Hewett, R; Alexakis, C; Farmer, A; Ainley, J; Chhaya, V; Poullis, A; Kang, J-Y
Abstract : Introduction: Eosinophilic oesophagitis (EoE) represents a chronic, immune-mediated oesophageal disease characterised clinically by symptoms related to oesophageal dysfunction and histologically by eosinophil-predominant inflammation. The incidence and prevalence of EoE are increasing and it tends to affect young male patients. Studies assessing of quality of life (QoL) in EoE outside the UK have conflicting results and QoL in the UK has not previously been assessed Method: Patients with EoE were asked via post to complete the Short Form (36) Health Survey (SF-36) which is a patient-reported survey of patient health. SF-36 is a short questionnaire with 36 items which measure eight multi-item variables: physical functioning (PF), role limitations due to physical problems (RP), pain (BP), general perception of health (GH), vitality (VT), social functioning (SF), role limitations due to emotional problems (RE) and mental health (MH). Patients also completed the Hospital odynophagia, dysphagia questionnaire (HODQ) (scored 0–50) and information on age, gender, comorbidity and medication use was also collected. A similar number of age and gender matched controls were also recruited Results: The patient response rate was 56%. 35 patients and 35 age and gender matched controls were recruited to the study (48 male, median age 39 years, range 17–68). Patients had a higher dysphagia score (7.25 +/- 5.6 vs. 0.34 +/- 1, p < 0.0001). There was no differences in PF ( p = 0 .35), RP ( p = 0 .24), BP ( p = 0 .2), GH ( p = 0 .07), VT ( p = 0 .18), SF ( p = 0 .17), RE ( p = 0 .06) and MH ( p = 0 .06). Multivariate logistic regression, controlling for age and gender, demonstrated that patients had higher rates of hay fever (odds ratio (OR) 4.3, Z=2.15, 95% confidence interval (CI) 1.14–16.5, p = 0 .03), antihistamine use (OR 25.5, Z=2.9 95% CI 2.9–217, p = 0 .003), proton pump inhibitor (PPI) use (OR 6.4, Z=2, 95% CI 1.1–37, p = 0 .04) but not asthma or eczema Conclusion: EoE is associated with higher rates of dysphagia and hay fever, but not asthma or eczema. EoE patients are more likely to use antihistamines or PPIs. PPIs are known to improve symptoms and histological inflammation in a sub set of EoE patients. EoE is not associated with a reduction in generic measures of quality of life. Further work is warranted to elucidate if treating EoE is also able to improve QoL Disclosure of interest: None Declared.